Konstruksi Paradigmatis Pemikiran Teologi Islam Kritis - Zainul Abas (IAIN Ponorogo, 2012)
An important question in this paper is how is paradigm construction of critical theological thought. To understand its construction, this paper shows paradigm shifting of thought of Islamic theology since classic era to contemporary. The shifting is since Khawarij growth that discuss about big sin, unbeliever, believer, heaven, and hell. Now, theological thought had grown and entered in various scientific paradigm. These themes are very variational too, even new thing that is nothing before. Critical theological thoughts belong to paradigms or new world views that is important for contemporary era. Critical theological thought in Indonesia had been stated by critical intelectuals such as Abdurrahman Wahid, Muslim Abdurrahman, Masdar F. Mas ’udi, and Kuntowijoyo. Paradigm of critical Islamic theology is an emancipatory thought on modern culture and society, for example critique of economics, politics, and structure. This thought starts from reaction of unjust social system. This thought starts from point of suffering in praxis. Its objective is to build social structure that freed human being from every oppression. Critical theological thought did not separate theory and practice, knowledge and action, theoritical rationality and practical rationality. This thought reflects critically something practice in historical sosial life.